Impact of the Implementation of a Postgraduate Mastology Course in the Province of Cienfuegos - Lidia Torres Ajá; Miriam Iglesias León; Carlos Zerquera Álvarez (Medisur)
Background: Cuban medical universities are aimed at the social formation of general practitioners who incorporate knowledge and skills that allow them to develop an appropriate professional performance when facing health issues, such as breast cancer. Promoting their postgraduate training is highly important. Objective: To describe the results of the implementation of a postgraduate Mastology course. Methods: Educational research conducted in the province of Cienfuegos on the benefits reported after the implementation (from 2000 to 2010) of a postgraduate Mastology course for general practitioners. The course was taught to a group of 15 specialists in each edition. The first class was full-time taught. The second and the third one were taught twice a week. Results: A qualitative leap in the health status of breast cancer in the province of Cienfuegos and in the professional performance of specialists in general medicine as to the diagnosis and therapeutic management of breast diseases was evident. In general, there was a contribution of new elements to the provincial health system. Conclusions: The postgraduate Mastology course raised the competence standard of general practitioners.